The Effect of the Discovery Learning Model and Reading Interest on Writing Skills - Novela Otri; Syahrul Ramadhan (Journal of World Science, 2026)
This study aims to explain the influence of the discovery learning model and reading interest on writing skills. This study uses qualitative research with an experimental method with a quasi-experiment type. The research population is all class X students of Senior High School 1 Koto XI Tarusan for the 2025/2026 school year with a total of 357 students. The sample of this study is class X E5 as an experimental class, and X E6 as a Control class. The research instrument used a questionnaire to find out reading interest and a performance test to find out students' writing skills. The results of the findings of this study are, First, the skill of writing the text of the observation results report taught using the model discovery learning higher than the skill of writing the text of the observation results report taught using the direct learning model. Second, the skill of writing the text of the observation results of students with high reading interest taught with the model discovery learning higher than students taught with a hands-on learning model. Third, the skills of writing the text of the observation results report for students with low reading interest taught with the model discovery learning higher than students taught with a hands-on learning model. Fourth, there is no interaction between models’ discovery learning and reading interest in writing skills in the text of student observation reports.